EVALUATION OF PROBITOIC POTENTIAL OF LACTOBACILLUS STRAINS FROM FERMENTED FOODS AND FEACES OF INFANTS - My Le, Nguyen Thi; Huong, Nguyen Thi (Vietnam Journal of Science and Technology, 2016)
Lactobacillus strains are a major part of the probiotics, microflora of the intestine and of fermented foods. The aim of this study was to evaluate the potential probiotics of six Lactobacillus strains (L. fermentum 39-183; L. plantarum subsp.plantarum P-8; L. casei ATCC 334; L. rhamnosus ATCC 8530, L. brevis KB 290 and L. fermentum JMC 7776). Probiotic properties such as acid tolerance, bile resistance, bacteriocin-like activity, cell surface hydrophobicity and antibiotic resistance were assessed. In vitro results obtained showed that all Lactobacillus strains tested were able to meet the basic requirements for probiotic functions as they demonstrated probiotic characteristics such as tolerance to pH 2.0 and 2% bile salt. All Lactobacillus strains inhibited the growth of E. coli, Staphylococcus aureus and Salmonella Typhi. Among strains tested, L. plantarum subsp.plantarum P-8 showing inhibitory is very promising with inhibition zone ranging between 6.5 to 12.7 mm. The results for cell surface hydrophobicity and susceptibility against antibiotics also showed that L. fermentum JMC 7776 and L. plantarum subsp.plantarum P-8 had higher cell surface hydrophobicity than the rests.  All Lactobacillus tested were resistant to vancomycin and susceptible to streptomycin. The results obtained in this investigation will be used to select potentially probiotic strains for in vivo study